THE STUDY OF NONVERBAL UNITS: THEORETICAL PERSPECTIVES AND RESEARCH DIRECTIONS - Barotova Mukhiba Orifovna (International Journal of Literature and Language Studies, 2026)
This article examines the history of nonverbal units research in world and Uzbek linguistics, their role in communication, and the main stages of scientific investigation. The study discusses the classification of nonverbal means, their functional characteristics, and their interaction with verbal communication. The scientific views of foreign and Uzbek scholars on nonverbal communication are comparatively analyzed, and promising directions for future research are identified.